On the spatio-temporal behavior of magnetohydrodynamic turbulence in a magnetized plasma - Lugones, Rodrigo (2016)
Using direct numerical simulations of three-dimensional magnetohydrodynamic turbulence, the spatio-temporal behavior of magnetic field fluctuations is analyzed. Cases with relatively small, medium, and large values of a mean background magnetic field are considered. The (wavenumber) scale dependent time correlation function is directly computed for different simulations, varying the mean magnetic field value. From this correlation function, the time decorrelation is computed and compared with different theoretical times, namely, the local non-linear time, the random sweeping time, and the Alfvénic time, the latter being a wave effect. It is observed that time decorrelations are dominated by sweeping effects, and only at large values of the mean magnetic field and for wave vectors mainly aligned with this field time decorrelations are controlled by Alfvénic effects.